PWE-322 Are we over-treating polyp cancers?. (22nd June 2015) - Nair, H; Ventham, N; Mulholand, C; Hallett, J; Stewart, A; Finneron, P; Potter, M; Mander, BJ; Dunlop, M; Din, F; Speake, D
Abstract : Introduction: The management and counselling of patients with polyp cancers can be technically challenging. Whilst identifying those at risk of residual or recurrent disease is important, it is undesirable to undertake potentially morbid resectional surgery when the risk of residual disease or recurrence is low. The aim of this study was to identify factors, which could better predict recurrence, thereby directing high-risk patients towards surgical resection and managing low-risk patients expectantly. Method: A retrospective review identified 282 polyp cancers from the South East Scotland Cancer Network over a 10-year period from 2003 to 2013). Data collected were polyp cancer pathology, follow up-period, disease-free survival and management strategy. All patients were discussed through the colorectal cancer multidisciplinary team and had endoscopic and radiological assessment. Results: Of the 282 polyp cancers identified, 85 (30.1%) underwent resectional surgery, 27 (9.6%) trans-endoscopic microsurgery and 195 (65.6%) had no further immediate treatment. This resulted in 222 patients on a watchful wait surveillance pathway. Median follow-up was 30.5 months for the watchful waiting group (range 1–97), 28 months for the resectional group (range 1–88). Overall, median follow up was 33 months (range 1–97). The most common reason for resectional surgery was an involved margin or adverse pathology. The overall median polyp size was 20mm (range 5–60 mm). In resectional surgery group, 91.2% had no residual disease, 8.8% had mural involvement, 7.7% nodal involvement and 4.4% had both. There was no 30-day mortality and morbidity was 16.1%. There were no local recurrences, 5 (5.9%) had distant recurrence, and 2 (2.4%) nodal recurrence. In the watchful wait group, 9 (4.1%) developed recurrence of which 5 underwent surgery and remain disease- free; the remainder were medically unfit for surgery. Conclusion: There were no recurrences in patients without adverse pathology (i.e. vascular invasion, high-grade dysplasia), where resection margins were >1 mm and both cross -sectional imaging and repeat endoscopy were clear. The majority of patients who had resectional surgery had no residual disease (>90%). Our data suggests favourable pathology but a close margin does not always mandate surgery and we have subsequently changed practise for these patients. Disclosure of interest: None Declared.